O Gênero Stylatractus Haeckel, 1887 (Radiolaria) em Sedimentos do Pleistoceno Superior - Holoceno da Margem Continental do Rio Grande do Sul - FAUTH, SIMONE BAECKER; LEMOS, VALESCA BRASIL (Pesquisas em Geociências, 2001)
The genus Stylatractus Haeckel, 1887 (Radiolaria, Actinommidae) is abundant in upper Pleistocene – Holocene sediments form the Rio Grande do Sul continental margin. Some species of this genus are important Cenozoic biostratigraphic tools. A detailed analysis of the species distribution in Core T18 (GEOMAR VII), as well as an estimate of the chronology of these sediments was done. A revision of Stylatractus is proposed, based on the growth patterns of the Actinommidae skeletons. Three species of Stylatratus were identified in the studied material: Stylatractus neptunus Haeckel, emend., Stylatractus pluto Haeckel n. comb. and Stylatractus nerinus n.sp. The occurrence of Stylatractus nerinus n.sp. suggests that these sediments were deposited in the upper Pleistocene. The Pleistocene-Holocene transition is established by the first occurrence of Stylatractus pluto Haeckel n. comb. The results obtained from Core T18 can be extended to other cores from the Rio Grande do Sul continental margin where the genus was reported.